The Dynamic Interplay between Context and the Language Learner - King, Jim (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
This edited volume offers a series of state-of-the-art conceptual papers and empirical research studies which consider how contextual factors at multiple levels dynamically interact with individuals to influence how they go about the complex business of learning and using a second language.